Loneliness dengan fear of missing out (fomo) pada generasi z perantau - Sisca Sintia Audria; Bawinda Sri Lestari; Herlan Pratikto (SUKMA : Jurnal Penelitian Psikologi, 2025)
Abstract This study aims to examine the relationship between loneliness and Fear of Missing Out (FOMO) among migrant Generation Z individuals. The study involved 140 Generation Z participants who were born between 2000-2012 and had migrant status in Surabaya. Data were collected using the UCLA Loneliness Scale and a Fear of Missing Out (FOMO) scale developed by the researcher based on relevant indicators. Data analysis using Spearman’s rho correlation yielded a correlation coefficient of r = 0.855 with a significance value of p = 0.000, indicating a positive and significant relationship between loneliness and Fear of Missing Out (FOMO). This finding suggests that higher levels of loneliness are associated with higher levels of Fear of Missing Out (FOMO) among migrant Generation Z individuals in Surabaya. Conversely, lower levels of loneliness are associated with lower levels of Fear of Missing Out (FOMO) among migrant Generation Z individuals in Surabaya. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara Loneliness dengan Fear Of Missing Out (FOMO) pada generasi Z perantau. . Penelitian ini menggunakan pendekatan kuantitatif korelasional. Subjek penelitian berjumlah generasi Z yang kelahiran tahun 2000-2012 dan berstatus perantau di Surabaya. Instrumen pengumpulan data menggunakan skala UCLA Loneliness Scale dan skala Fear Of Missing Out (FOMO) yang dikembangkan oleh peneliti berdasarkan indikator. Analisis pada penelitian menggunakan korelasi Spearman’s rho menghasilkan nilai koefisien r = 0,855 dengan signifikansi p = 0,000 yang menunjukkan terdapat hubungan positif dan signifikan antara Loneliness dengan Fear Of Missing Out (FOMO). Artinya, semakin tinggi loneliness maka semakin tinggi Fear Of Missing Out (FOMO) pada generasi Z perantau di Surabaya. Sebaliknya, semakin rendah loneliness maka semakin rendah Fear Of Missing Out (FOMO) pada generasi Z perantau di Surabaya.